Intraoperative Radiotherapy for Resected Pancreatic Cancer: A Multi-Institutional Retrospective Analysis of 210 Patients - Ogawa, Kazuhiko; Karasawa, Katsuyuki; Ito, Yoshinori; Ogawa, Yoshihiro; Jingu, Keiichi; Onishi, Hiroshi; Aoki, Shinichi; Wada, Hitoshi; Kokubo, Masaki; Etoh, Hidehiro; Kazumoto, Tomoko; Takayama, Makoto; et al. (International journal of radiation oncology, biology, physics, 2010)
To retrospectively analyze the results of intraoperative radiotherapy (IORT) with or without external beam radiotherapy (EBRT) for resected pancreatic cancer. The records of 210 patients treated with gross complete resection (R0: 147 patients; R1: 63 patients) and IORT with or without EBRT were reviewed. One hundred forty-seven patients (70.0%) were treated without EBRT and 114 patients (54.3%) were treated in conjunction with chemotherapy. The median doses of IORT and EBRT were 25 Gy (range, 20–30 Gy) and 45 Gy (range, 20–60Gy), respectively. The median follow-up of the surviving 62 patients was 26.3 months (range, 2.7–90.5 months). At the time of this analysis, 150 of 210 patients (71.4%) had disease recurrences. Local failure was observed in 31 patients (14.8%), and the 2-year local control rate in all patients was 83.7%. The median survival time and the 2-year actuarial overall survival (OS) in all 210 patients were 19.1 months and 42.1%, respectively. Patients treated with IORT and chemotherapy had a significantly more favorable OS than those treated with IORT alone (p = 0.0011). On univariate analysis, chemotherapy use, degree of resection, carbohydrate antigen 19-9, and pathological N stage had a significant impact on OS and on multivariate analysis; these four factors were significant prognostic factors. Late gastrointestinal morbidity of NCI-CTC Grade 4 was observed in 7 patients (3.3%). IORT yields an excellent local control rate for resected pancreatic cancer with few frequencies of severe late toxicity, and IORT combined with chemotherapy confers a survival benefit compared with that of IORT alone.